Waiting to Be Heard: Fairness, Legal Rights, and Injustices the Deaf Community Faces in Our Modern, Technological World - Justin Chavez (Washington University Global Studies Law Review, 2018)
This note will examine the existing access to legal aid, employment, recourse, and education in various deaf cultures and societies. The goal is a comparative study into how the DHH communities are accepted, valued, and prioritized in different countries, and how that translates into legal infrastructure, in the form of governmentally-mandated statues, regulations, public accommodations, and legal education. This will consist of a brief history into the recognition, labeling, and acceptance of deaf citizens in ancient and modern cultures, the path to a society’s awareness and eventual recognition of deaf citizens, and how the various levels of awareness differ among regions and countries. The glimpse into varying cultures will also reveal the differences in legal systems, the effects those systems have on deaf culture, and how accessible those legal remedies are for deaf citizens. This note will focus on analyzing existing judicial infrastructures, potential barriers to justice, and the basic legal rights of a deaf person, in our modern, technological, and digital world.
Keywords: Equity; Deaf; deafness; technology; technological advancements; law; injustice